Maintaining Momentum to 2015 : An Impact Evaluation of Interventions to Improve Maternal and Child Health and Nutrition in Bangladesh - Operations Evaluation Department (Washington, DC: World Bank, 2012)
This report addresses the issue of what publicly-supported programs and external assistance from the Bank and other agencies can do to accelerate attainment of targets such as reducing infant mortality by two-thirds. The evidence presented here relates to Bangladesh, a country which has made spectacular progress but needs to maintain momentum in order to achieve its own poverty reduction goals. The report addresses the following issues: (1) What has happened to child health and nutrition outcomes and fertility in Bangladesh since 1990? Are the poor sharing in the progress which is being made? (2) What have been the main determinants of maternal and child health outcomes in Bangladesh over this period? (3) Given these determinants, what can be said about the impact of publicly and externally-supported programs - notably those of the World Bank and DFID - to improve health and nutrition? (4) To the extent that interventions have brought about positive impacts, have they done so in a cost effective manner?